THE EFFECT OF CARBON ON THE ELECTRIC PROPERTIES OF POLYETHYLENETEREPHTHALATE - BACHARI, THAMIR SALMAN (Al-Qadisiyah Journal of Pure Science, 2017)
The electrical properties of polymer bulk films have done from prepared PET (polyethylene terephalate) of water drinking bottle as paste and mixed with different percentages by weight (wt%) Carbon (C) on clean glass substrates. This investigation exhibits dependence on the structure of the polymer. The polymer bulk strip films showed different electrical properties, which depend on the film thickness and the applied voltage, PET characterization and diagnosis were carried out by infrared spectrophotometer (IR) and differential scanning calorimeter (DSC). The I-V characteristics of the films were measured at applied voltage (150) volt d.c. and the effect have been discussed, the electrical resistivity (Ï) and the electrical conductivity (Ïƒ) were measured depend on the percentage of film constituent.. The calculated activation energy is equal to 5.6x10–4 eV at PET0.02C0.002.